Improving Modern Pondok Students' Arabic Language Skills in Indonesia: Language Institutions as Language Improvement Central - Ilyas Ilyas; Muh. Rasmi; Muhammad Rusydi (AL-ISHLAH: Jurnal Pendidikan, 2024)
Islamic boarding schools, or pesantrens, have long played a significant role in the educational landscape of Indonesia, particularly in fostering religious and linguistic knowledge. This research focuses on three modern Islamic boarding schools in Indonesia: Al-Junaidiyah Biru in Bone Regency, IMMIM Putra Makassar in South Sulawesi, and Darussalam Gontor in Ponorogo. Central to the study is the role of the Language Improvement Centre (LIC) at these institutions, which demonstrates crucial innovations in Arabic language learning. The research employs a qualitative method. Data were gathered through interviews with educators, observations of classroom practices, and analysis of curriculum documents. This methodology provided a comprehensive understanding of the LICs' impact on Arabic language education. The study identifies several key functions of the LICs: a) designing Arabic language learning programs that align with the skills students are expected to master; b) conducting regular and organized assessments of students' Arabic language proficiency; and c) developing new teaching approaches based on these assessments. These roles collectively contribute to a robust enhancement of Arabic language learning within the pesantrens. The findings highlight the LICs' effectiveness in fostering a rich and innovative Arabic language learning environment. This research underscores the importance of these centers in the broader context of Islamic education in Indonesia. Future research could explore further innovations introduced by LICs and assess their long-term impacts on students' proficiency and engagement with the Arabic language.